PENERAPAN EFFLEURAGE MASSAGE UNTUK PENURUNAN INTENSITAS NYERI PUNGGUNG PADA ASUHAN KEPERAWATAN IBUHAMIL PRIMIGRAVIDA TRIMESTER III DI BIDAN PRAKTEK MANDIRI TATI KARWATI A.MD.KEB - Alfika Nurjanah, Siti; Anggi, Geuis; Darmayanti; Ati Nurhayati, Nung (Jurnal Kesehatan An-Nuur, 2025)
The incidence of back pain in pregnant women in the world is 70-86%, while in Indonesia pain is as much as 18% of 261 pregnant women. The impact of back pain if not treated will experience discomfort and sleep disorders. Handling back pain in pregnant women can be done non- pharmacologically, one of which is with the Effleurage Massage technique. The purpose of this case study is to apply the application of effleurage massage to reduce the intensity of back pain in nursing care for primigravida pregnant women in the third trimester. This case study uses a descriptive method with a nursing care process approach. The results of the case study obtained the main complaint of back pain accompanied by sleep pattern disorders and a nursing diagnosis was raised with the problem of discomfort disorders. The focus of the intervention is aimed at improving the status of comfort and sleep patterns through Massage the application of effleurage massage.